Building convergence in science, programs, and policy actions on child undernutrition: symposium rationale and overview. - Menon P; Stoltzfus RJ; Menon, Purnima; Stoltzfus, Rebecca J (Advances in Nutrition, 2012)
Childhood stunting and wasting are often portrayed as relatively distinct manifestations of undernutrition. Little is known about how children progress from one manifestation of undernutrition to another as they grow older, nor how intervention strategies need to consider the potential overlap of these manifestations of undernutrition. While much is known about the causes of growth faltering in general, much less is known about which pre-disposing contextual and biological factors cause children to become stunted as opposed to wasted or both. Increasingly, nutrition researchers have tended to focus on one form of malnutrition or the other, lacking an integrated framework for understanding both phenomena. Similarly, some practitioner communities focus on prevention of stunting while others focus on recuperative treatment of wasting. The fragmentation of interests and perspectives on childhood undernutrition has negative consequences for advocacy efforts that aim to bring attention and resources to child nutrition across the globe. It also has serious implications for how children worldwide receive nutrition interventions and services. The symposium aimed to bring together a set of speakers from academic, practice and policy communities to discuss and debate these issues.